Effect of Pollarding on Foliar Chemistry of Terminalia arjuna - Rai, Shruti; Aggarwal, K.K.; Babu, C.R. (Asian Journal of Chemistry, 2010)
Temporal and spatial distribution of plant's foliage generate microclimatic conditions that influence the chemistry of foliage, which in turn regulate the herbivory and foraging behaviours of insects. These aspects have not been studied with respect to tasar silkworm and its host plant, Terminalia arjuna. Pollarding reduces all the foliar constituents of T. arjuna, particularly the defense chemicals thus confirming the role of canopy in foliar chemistry. Pollarding of trees simulates low light conditions in the canopy of T. arjuna with respect to variation in foliar constituents. Thus in terms of antinutrients, pollarding has beneficial effect for tasar silkworm rearing.